Implementation of Problem Solving Learning Model to Self Directed Learning of High School Students in Chemical Equilibrium Materials - Renda Suri Pratimi (Saniya Institute, 2024)
The purpose of this study is to determine the effect and interaction between learning chemical equilibrium learning and the problem-solving model on the motivation of learning equilibrium learning in terms of self-direct learning capabilities (SDL). This study uses a pseudo experimental research design, Posttest Only Nonequivalent Control Group Design. Sampling uses cluster random sampling techniques. The sample consisted of 2 experimental and control classes of IT Nufi Selong High School students. Research data is a test data from self-direct learning results that include self -management, desire for learning and self-control. Another test used is a cognitive test in the form of questions about chemical equilibrium. The test results showed that the highest value of the SDL test in the experimental class was 132 with the highest standard SDL was 133. Whereas the control class obtained the highest value of SDL 117. This had a good impact on learning outcomes that showed a significant difference in learning outcomes in both classes namely the average experimental class value was 88, 1 and in the control class the average value obtained was 66.4. With this it can be concluded that there is an influence of the Problem-Solving model in terms of students' self-direct learning capabilities. And there is a positive interaction between the use of the model of SDL and student learning outcomes in the experimental class.